Implementasi Community Based Tourism dalam Mewujudkan Kemandirian Desa - Raja Ahmad Fernando; Hanny Purnamasari; Lina Aryani (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine and analyze the Implementation of Community Based Tourism in Creating Village Independence (Case Study of Cibitung Tourism Village, Ciater District, Subang Regency). The theory used in this study is the principles of implementing Community Based Tourism which consists of Economic Principles, Social Principles, Cultural Principles, Environmental Principles, and Political Principles. The method in this research is descriptive qualitative. Data collection techniques were carried out through interviews, observation and documentation, then the data were analyzed using the concept of data analysis which includes data reduction, data presentation and drawing conclusions. The results and discussion show that the implementation of Community Based Tourism in Cibitung Tourism Village in economic principles shows good results with an increase in income from the community, social principles also lead to good things because there is community pride in Cibitung Tourism Village, then the cultural principle does not run smoothly. optimal given the lack of massive information on several social media pages and print media, the environmental principles of the Cibitung Tourism Village use the Ecovillage concept and political principles, it is found that there is apathy from the government which has minimal implementation of policies that can be self-reliant for people who are able to manage the Cibitung Tourism Village tourism industry